Effect of hydrocolloid type on physiochemical properties of nonfat drinkable yogurt fermented with ropy and non-ropy yogurt cultures - Gad, Ahmed S; Mohamad, Sahar H. S. (Comunicata Scientiae, 2014)
Abstract Drinkable yogurt is defined as a dairy-based yogurt that is drinkable and in a liquid form that may or may not include fruit or fruit flavoring. Mouthfeel defects may be affected by processing conditions, starter cultures, and stabilizer selection. This research was investigated the effect of hydrocolloid type (gelatin, carboxymethylcellulose and high methoxy pectin) on the sensory characteristics and rheological properties of drinkable yogurts fermented with nonropy and ropy cultures. The results demonstrate that gelatin-stabilized drinkable yogurt fermented with nonropy and ropy cultures had significantly higher acidity and protein content. Yogurt stabilized with gelatin was the thickest yogurts with lack of whey separation and had a positive significant effect on the sensory characteristics. Drinkable yogurt stabilized with CMC proved to be completely unacceptable as a stabilizer for the yogurt drink. A better understanding of factors contributing to the physical and structural attributes may allow manufacturers to improve the quality of yogurt.